Private rights and public responsibilities: recent developments in Scots water law - Hendry, S (Foundation for Law, Justice and Society, 2013)
Water law has been the subject of considerable attention in the Scottish Parliament since its re-establishment in 1999, with five Water Acts passed in that time. This policy brief examines these recent reforms and considers whether there has been a shift from private rights to private responsibilities, or perhaps, from private rights to public rights, over water resources in Scotland. The brief will also consider what lessons may be learned in England from the introduction in Scotland of limited competition in retail services in the business sector, also now part of the current reform package being developed in England. The policy brief concludes that water has, de facto if not explicitly in the law, moved from the private to the public domain. Holders of land which includes water will still have some special status, but the power to control the resource as a matter of public interest is incontrovertible.